EFEKTIVITAS PEMBELAJARAN FULLY DARING TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA - Hr, Bq. Malikah; Pratama, Indah Arry; Munawarah, Pyo Apriliana (Media Pendidikan Matematika, 2020)
The purpose of thisÂ researchÂ wereÂ toÂ describe: 1)Â the effect of fully online learning to theÂ mathematical reasoning abilities of students; 2) the response of the students to the application ofÂ fully online learning.Â The research wasÂ a mixed-method using quantitative and qualitative methodsÂ withÂ oneÂ group pretest-posttestÂ design.Â There wereÂ 32Â studentsÂ ofÂ class XIÂ MIA MA NW Wanasaba, WanasabaÂ Sub-District,Â East Lombok RegencyÂ as theÂ sample.Â InstrumentÂ ofÂ thisÂ research wasÂ theÂ mathematical reasoning abilitiesÂ essayÂ testÂ consists of 10 questions on learning materials of limit function, observation and interviews. The quantitative data analysis usingÂ descriptive statistics withÂ paired sampel t-test. The results of this research showed that: 1) according to the results of data analysis, it was discovered the value of Sig. (2-tailed) was 0.000 < 0.05,Â it means thatÂ H0Â was rejectedÂ andÂ HaÂ was accepted,Â this indicated thatÂ there was a differenceÂ betweenÂ the pretestÂ and posttestÂ average.Â Based on the descriptive statistics, the average of pretest score was 71.03 higher than the posttest score was 59.97.Â It can be concluded thatÂ the fully online learningÂ was no more effectiveÂ to theÂ mathematical reasoning abilities of students. 2) there were 16% of the students gave a positive response to the application ofÂ fully online learning, 84% of the others prefer the blended learning and students gave a less positive response to the application ofÂ fully online learningÂ and it was considered less helpful in practicing the mathematical reasoning abilities of students.